The effect of using different levels of dry yeast and acetic acid on Japanese quail fattening indicators - Taleb, Hassan Mohamad (Journal of agricultural, environmental and veterinary sciences, 2022)
The study was carried out on 180 chicks of Japanese quail in the poultry of Al-Nour - Jerrod, the birds were distributed since the beginning of the experiment into (9 groups at a rate of 20 chicks for each group and each group was distributed to two repeats each repeating 10 chicks) of one day old. All the conditions of shelter and care were the same for all groups during the care period, which lasted from the age of one day to the age of 6 weeks. As for the feeding of the birds of the different groups, they were different as follows: It included nine feed mixtures, each one differing from the other with the level of addition of dry yeast and the level of addition of vinegar acid (3 x 3).The first factor: the effect of the level of crude protein in mixtures, as it decreased and raised by 10% than it was in (NRC1994).The second factor: the effect of the level of dry yeast in the mixtures, as they were in the following proportions (0.0, 0.05 and 0.1%).The search is (3 × 3).The results of the research showed the following:Effect of adding dry yeast: the addition of dry yeast in mixtures resulted in a significant superiority with: average live weight index and production number.The effect of adding acetic acid: adding acetic acid to the mixtures resulted in a significant superiority: the average live weight index and the production number.The effect of the interaction between dry yeast and vinegar acid: The interaction is positive when using crude protein and acetic acid, as it gave the best performance and the highest economic return.
Keywords: Japanese quail; Dry Yeast; Acetic Acid; Food Conversion; Fattening quil